Experiments on the Different Numbers of Bidders in Sequential Auctions - Gunay, Hikmet (2024)
In a second-price sequential auction with global and local bidders, we analyze the correct selling order of goods when the number of bidders in each leg of the auction is different with laboratory experiments. Theoretically, selling the good with a large number of bidders last should generate an (almost) efficient outcome but selling it first should result in an inefficient outcome with a positive probability. Our experimental results show that selling that good last generates a more efficient outcome than selling it first. Hence, the experimental results show that the selling order has to be taken into account while designing a sequential auction.